The species specific of 3 microRNA markers in saliva. (December 2015) - Peng, D.; Li, Z.; Wang, L.; Su, Q.; Jiang, Y.; Zhu, J.; Wang, H.; Mao, J.; Liang, W.; Zhang, L.
Abstract: MicroRNAs (miRNAs) have been proven to exist in forensically relevant body fluids. However, we need to know whether the result would be influenced by other species' saliva. This study aims to analyze the expression levels of 3 miRNA markers in different species, including Homo sapiens, Felis catus, Canis lupus familiaris, Cavia porcellus, Sus scrofa, Mus musculus, Oryctolagus cuniculus, Bos taurus, Capra hircus . MiRNAs were extracted using Qiagen kits from 9 kinds of different species' saliva. Reverse transcription and quantitative PCR was performed with SYBR ® Green with water as a negative control and U6b as a reference. Some of target miRNAs were found to be expressed in different body fluids of both human and animals. Saliva microRNA markermicroRNA200c (miR-200c) which is highly expressed in human being saliva[1] has a high level of expression in other species. Our results suggest that species specificity should be analyzed before identifying crime scene evidence because the stains may be mixtures with some other species. We propose to carry on species specific research when seeking a new candidate miRNA marker for forensically relevant human fluids.